Synthesis and anti-tubercular activity of N2-arylbenzo[g]isoquinoline-5, 10-dione-3-iminium bromides. Issue 6 (14th January 2016) - Rotthier, G.; Cappoen, D.; Nguyen, Quang Trung; Dang Thi, Tuyet Anh; Mathys, V.; Nguyen, Van Tuyen; Huygen, K.; Maes, L.; Cos, P.; Abbaspour Tehrani, K.
Abstract : The synthesis of a new class of benzo[ g ]isoquinoline-5, 10-diones carrying an amidine functionality and their anti-mycobacterial activities against Mycobacterium tuberculosis H37Rv are reported. Abstract : Tuberculosis has remained a challenge for medicinal chemists worldwide. In the framework of a collaborative program to identify and evaluate novel antitubercular candidate compounds, the biological properties of benzo[ g ]isoquinoline-5, 10-diones have been found to be very promising. In this paper we have further expanded the library by incorporation of an amidinium moiety into the benzo[ g ]isoquinoline-5, 10-dione scaffold. The presence of this functional group also increased the solubility of the quinones in polar solvents. To this purpose N 2 -arylbenzo[ g ]isoquinoline-5, 10-dione-3-iminium bromides were synthesized in a straightforward way by means of a reaction of anilines with 2-(bromomethyl)-3-(cyanomethyl)-1, 4-dimethoxynaphthalene. Following the biological evaluation, N 2 -(4-chlorophenyl)-5, 10-dioxobenzo[ g ]isoquinoline-3(2 H )-iminium bromide (MIC = 1.16 μM, CC50 = 28.51 μM, SI = 24.58) was selected as the most promising representative. Apart from the nano-molar anti-mycobacterial activity, the compound was able to target intracellular residing Mycobacterium tuberculosis and the susceptibility of a multi-drug-resistant strain towards the compound was confirmed.